Who consumes most of the cannabis in Canada? Profiles of cannabis consumption by quantity. (1st December 2019) - Callaghan, Russell C.; Sanches, Marcos; Benny, Claire; Stockwell, Tim; Sherk, Adam; Kish, Stephen J.
Highlights: Study pooled Waves 1–3 of the 2018 Canadian National Cannabis Survey ( n  = 18, 900). Surveys assessed cannabis use by quantity across seven major cannabis-product types. A standard joint measure was created, based on physical production equivalencies. The upper 10% of Canadian cannabis users accounted for 66% of all cannabis consumed. Abstract: Aim: To establish whether the population-level pattern of cannabis use by quantity is similar to the distributions previously reported for alcohol, in which a small subset of drinkers accounts for a majority of total population alcohol consumption. Method: The current study pooled Waves 1–3 of the 2018 National Cannabis Survey ( n  = 18, 900; 2584 past-three-month cannabis users), a set of stratified, population-based surveys designed to assess cannabis consumption and related behaviors in Canada. Each survey systematically measured self-reported cannabis consumption by quantity across seven of the major cannabis-product types. In order to enable the conversion of self-reported consumption of non-flower cannabis products into a standard joint equivalent (SJE: equal to 0.5 g of dried cannabis), we created conversion metrics for physical production equivalencies across cannabis products. Results: Similar to the findings in the alcohol literature, study results show that cannabis consumption is highly concentrated in a small subset of users: the upper 10% of cannabis users accounted for approximately two-thirds of all cannabis consumed in the country. Males reported consuming more cannabis by volume than females (approximately 60% versus 40%), with young males (15–34 years old) being disproportionately represented in the heaviest-using subgroups. Conclusions: Most of the cannabis used in Canada is consumed by a relatively small population of very heavy cannabis users. Future research should attempt to identify the characteristics of the heaviest-using groups, as well as how population-level cannabis consumption patterns relate to the calculus of cannabis-related harms in society.